In Vitro Anti-bacterial Activities of Aqueous, Ethanol and Chloroform Crude Extracts of Olinia rochetiana and Vernonia myriantha - Gashaw Nigussie; Ayana Erdedo; Sintayehu Ashenafi (Journal of Tropical Pharmacy and Chemistry, 2020)
In the past with the advent of antibiotics, bacterial diseases have been under control. However rapid spread of antibiotic-resistant this success is reversing and searching for newer antibacterial agents is currently a top priority. This study was, thus, aimed at assessing the anti-microbial activities of two traditional medicinal plants: Vernonia myriantha and Olinia rochetiana. The crude extracts were tested for their in vitro antibacterial activities and phytochemical content. The extracts were tested against selected 3 clinical and 4 standard test bacterial strains by using agar well-diffusion method and the minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC). The ethanol leaves and stem-bark extracts of O. rochetiana inhibited the growth of all bacterial strains at a concentration of 250mg/mL. The inhibition zones ranged from 20.33±0.57mm for clinical Pseudomonas aeruginosa to 25.66±0.57mm for standard Salmonella typhi strains. The values for these same extracts were 20.66±2.51mm and 24.33±1.15mm for standard P. aeruginosa and Staphylococcus aureus strains respectively. The chloroform extract was similarly effective against all of the strains with inhibition zones between 19.00±1.73mm against P. aeruginosa and 22.66±2.51mm for S. aureus. Comparatively, the ethanol extract of O. rochetiana had the highest MIC (7.81mg/mL) and MBC (62.50mg/mL) were noted against P. aeruginosa. On the other hand, chloroform extract of O. rochetiana leaf showed the highest MIC (15mg/mL) and MBC (125mg/mL) were recorded against P. aeruginosa. The ethanol extract of V. myriantha showed growth inhibition only on S. aureus (21.00±1.7mm). Both plants tested for terpenoids and glycosides showed positive result, but none for resin.